2017
DOI: 10.3390/molecules22020213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Benzimidazole Derivatives and Analogs Targeting the NLRP3 Inflammasome

Abstract: A series of benzo[d]imidazole analogues of thiabenzole were synthesized and their anti-inflammatory activities toward NLRP3 (nucleotide-binding domain leucine-rich repeat containing protein family, pyrin domain-containing 3, also known as cryopyrin or NALP3) inflammasome were evaluated in vitro. Two lead compounds, TBZ-09 and TBZ-21, were identified by anti-production of IL-1β. In the second round of biological evaluation, based on the lead, 34 more compounds were synthesized and their in vitro anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A broader series was synthesized consisting of analogues retaining an EWG in this position, as well as alternatives to the benzimidazole scaffold. 310 The most potent compound of this series, AI-33 ( Fig. 4D ), has an IC 50 of only around 10 μM; however, this series does represent a potential new approach to inhibiting NLRP3-dependent IL-1β release.…”
Section: Contribution Of Inflammasomes To Cns Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…A broader series was synthesized consisting of analogues retaining an EWG in this position, as well as alternatives to the benzimidazole scaffold. 310 The most potent compound of this series, AI-33 ( Fig. 4D ), has an IC 50 of only around 10 μM; however, this series does represent a potential new approach to inhibiting NLRP3-dependent IL-1β release.…”
Section: Contribution Of Inflammasomes To Cns Diseasementioning
confidence: 97%
“…308 Structurally similar thiabendazole analogues 309 can also act as anti-inflammatory agents. 310 An early lead, TBZ-09, inhibits the release of IL-1β and exhibits the structural feature of an electron withdrawing group (EWG) at position 5 of the benzimidazole core ( Fig. 4D ).…”
Section: Contribution Of Inflammasomes To Cns Diseasementioning
confidence: 99%
“…It is well established that NLRP3 is a critical component of NLRP3 inflammasome and being involved in inflammatory diseases. 5,19,20 We first determined the expression of NLRP3 and the therapeutic potential of nodakenin. As shown in Figure 3A, the results showed that an obvious rise of protein level of NLRP3 expression by immunohistochemistry is primarily located in renal tubules after ischaemiareperfusion injury.…”
Section: Nodakenin-inhibited Nlrp3 Inflammasome Activation In Vivomentioning
confidence: 99%
“… 18 Moreover, Pan et al synthesized novel benzimidazole derivatives and identified, in vitro, out of 34 compounds, several with an anti-inflammatory effect. 19 Faour et al also evaluated four series of newly synthesized bipyrazoles for their anti-inflammatory and analgesic activities. Two compounds showed superior anti-inflammatory activity compared to diclofenac and similar analgesic activity with minimal ulcerogenic side effect.…”
Section: Introductionmentioning
confidence: 99%